Prevalence, incidence, and case fatality of tuberculous meningitis in adults living with HIV: a systematic review and meta-analysis - Xue Chen; Jiaqi Wei; Mei Zhang; Bin Su; Meixin Ren; Miaotian Cai; Yulin Zhang; Tong Zhang (BMC Public Health, 2024)
Abstract Background Tuberculous meningitis (TBM) emerges as a grave complication of tuberculosis in people living with HIV (PLWH). The diagnosis and treatment of TBM pose significant challenges, leading to elevated mortality rates. To comprehensively grasp the epidemiological landscape of TBM in PLWH, a systematic review and meta-analysis were meticulously undertaken. Methods We performed a comprehensive search in PubMed, Embase, and Web of Science from database inception to September 19th, 2023, with no limitations on the publication type. The search terms were HIV/AIDS terms (AIDS OR HIV OR PLWH) and TBM-related terms (tuberculous meningitis OR TBM). Studies included in this meta-analysis evaluated the incidence of TBM among PLWH, or we were able to calculate the incidence of TBM among PLWH from the research. Results The analysis revealed that the prevalence of TBM among PLWH was 13.6% (95% CI: 6.6–25.9%), with an incidence rate of 1.5 cases per 1000 persons per year. The case fatality rate was found to be 38.1% (95% CI: 24.3–54.1%). No significant publication bias was observed. Meta-regression analysis identified the proportion of females and finance situation as factors influencing the outcomes. Conclusions Our study highlights TBM as a prevalent opportunistic infection that targets the central nervous system in PLWH. The elevated case fatality rate is especially prominent among PLWH in impoverished regions, underscores the pressing necessity for enhanced management strategies for PLWH suffering from TBM. Trial registration PROSPERO; No: CRD42022338586.